Treatment of Diabetic Foot with Autologous Stem Cells: A Meta-Analysis of Randomized Studies - Jiezhi Dai; Chaoyin Jiang; Hua Chen; Yimin Chai (Hindawi Limited, 2020)
Background. This meta-analysis was to evaluate the efficacy of autologous stem cell administration for the treatment of diabetic foot. Methods. The electronic databases included PubMed, EMBASE, BIOSIS, Cochrane central, and Google Scholar internet, last updated on May 30, 2019. Evaluated outcomes included the rate of wound healing and amputation. Dichotomous outcomes were described as risk ratios (RR) with 95% confidence intervals (CIs). Statistical analysis was performed with RevMan 5.0 software and STATA 10.0 software. Results. Eight randomized controlled trial (RCT) studies were included in this study. The meta-analysis showed a lower amputation (RR 0.25, 95% CI 0.11 to 0.54, I2=0) and a higher wound healing rate (RR 2.05, 95% CI 1.67 to 2.51, I2=4) in the cell therapy group compared with control. Conclusion. This meta-analysis supports the effective role of stem cell therapy in promoting wound healing and decreasing rate of amputation in diabetic foot. In the future, more high quality and well-designed studies are need.